Evaluación técnico financiera de los efectos de los modificadores de permeabilidades relativas en el campo la Cira Infantas (2019)
For this project, it carries out a technical-financial evaluation of the effects of a chemical solution consisting of the injection of relative permeability modifiers to reduce the relative permeability of water and thereby minimize the water cut. By means of a numerical simulation of conceptual type different scenarios were evaluated in which the treatment of relative permeability modifiers was applied taking into account the variables of relative water permeability and the radius of invasion of the polymer. The financial evaluation allows to define the best scenario, in which the expenses corresponding to the production of water, are considerably reduced and in this way determine the financial viability of the project with respect to a base case. Through the financial indicator of Net Present Value (NPV), the profitability of this project is evaluated.